2021
DOI: 10.1155/2021/5856730
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educational Intervention on the Improvement of Nontechnical Skills in Circulating Nurses

Abstract: Background. Nontechnical skills are necessary for clinicians’ safe performance and prevention of errors in the operating room. Educational intervention is a useful way to improve these skills, which are a vital area for improvement. Circulating nurses are surgical team members whose work depends heavily on using nontechnical skills. This study is aimed at assessing the effect of an educational intervention on the improvement of circulating nurses’ nontechnical skills. Methods. This semiexperimental study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Indeed, a major barrier to the implementation of training for experienced staff is that individuals may not believe they need to improve and thus see the training as unnecessary. 5 Importantly, because our participants reported learning new techniques that would support their RAS practice in the future, despite their already high confidence, this adds further weight to the value of approaches similar to ours. One staff member commented that the RAS Olympics provided her team with the opportunity to excel in tasks and perform better than they would have expected in a real environment during a surgical case.…”
Section: Limitationsmentioning
confidence: 73%
See 2 more Smart Citations
“…Indeed, a major barrier to the implementation of training for experienced staff is that individuals may not believe they need to improve and thus see the training as unnecessary. 5 Importantly, because our participants reported learning new techniques that would support their RAS practice in the future, despite their already high confidence, this adds further weight to the value of approaches similar to ours. One staff member commented that the RAS Olympics provided her team with the opportunity to excel in tasks and perform better than they would have expected in a real environment during a surgical case.…”
Section: Limitationsmentioning
confidence: 73%
“…It is possible that this was due to a small sample, ceiling effects with the scale or responses, or overconfidence in skills. Indeed, a major barrier to the implementation of training for experienced staff is that individuals may not believe they need to improve and thus see the training as unnecessary 5 . Importantly, because our participants reported learning new techniques that would support their RAS practice in the future, despite their already high confidence, this adds further weight to the value of approaches similar to ours.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Reported positive attitudes toward the use of surgical safety checklists in pediatric surgeries (20) also show that operating room staff does well in showing their nontechnical skills in these operating rooms. Several studies have shown some poor teamwork skills in operating room practitioners in Iran (21)(22)(23)(24). However, all of these studies were conducted at the individual level and on different surgery types than pediatric.…”
Section: Discussionmentioning
confidence: 99%
“…Asepsis means without the presence of pathogens and implies that an object does not convey pathogenic microorganisms (2). One of the circulating nurses' most important duties is supervising aseptic practices, which require proper nontechnical skills (10)(11)(12). Supervising aseptic practices could be helpful in preventing surgical site infections (13), which are known as significant concerns for the surgical team (14).…”
Section: Introductionmentioning
confidence: 99%